Fair Legal Protection for Bankruptcy Respondent Debtors - Sosilo, Peter; Nurjaya, I Nyoman; Prasetyawati, Endang; Nasution, Krisnadi (Batulis Civil Law Review, 2025)
Introduction: One of the important principles regulated in the Bankruptcy Law and Postponement of Debt Payment Obligations is the Going Concern Principle, which can enable a business entity or individual to run again even though it has fallen into bankruptcy, in this case the assets belonging to the debtor can be managed by the curator to obtain income as an effort to fulfill the debtor's debts. gradually to creditors.Purposes of the Research: This research aims to analyze just legal protection for debtors who are respondents to bankruptcy in the Bankruptcy Law and Postponement of Debt Payment Obligations.Methods of the Research: The type of research used is normative juridical, examining positive legal norms with the concept of law as it is written in the book, namely by conducting studies of statutory regulations and literature studies.Results Main Findings of the Research: The application of the principle of business continuity in bankruptcy cases and postponing debt payment obligations is within the framework of legal protection for debtors and has a positive impact on increasing the company's economic value which in turn is used to pay debts to its creditors.